Pelatihan Pencak Silat Di Desa Ciklapa Tahun 2022 - Rama Cipta Prasetia; Dwi Septian; Abdul Hafid (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
Thematic Real Work Lectures (KKN) are KKN whose activity programs focus on certain areas according to social problems and the direction of development policies implemented by certain regional governments. STKIP Darussalam Cilacap organizes a Real Work Lecture program using the thematic method. KKN-T is intended to develop a spirit of empathy and concern for problems that occur in society. work program with the theme "Pencak Silat Training" with the hope of being able to raise awareness of the importance of waste knowledge and how to use it. Apart from that, waste can also boost the school economy, by selling non-organic waste directly or making handicrafts which of course will increase the selling price. For this reason, the author also created a product as a first step, with the hope that the school would develop other products to increase selling prices and as a form of student creativity training.